(untitled) (Global Journal of Computer Science and Technology, 2023)
This study collected pre-processed dataset of chest radiographs formulated a deep neural network model for detecting abnormalities It also evaluated the performance of the formulated model and implemented a prototype of the formulated model This was with the view to develop a deep neural network model to automatically classify abnormalities in chest radiographs In order to achieve the overall purpose of this research a large set of chest x-ray images were sourced for and collected from the CheXpert dataset which is an online repository of annotated chest radiographs compiled by the Machine Learning Research group Stanford University The chest radiographs were preprocessed into a format that can be fed into a deep neural network The preprocessing techniques used were standardization and normalization The classification problem was formulated as a multi-label binary classification model which used convolutional neural network architecture for making decision on whether an abnormality was present or not in the chest radiographs The classification model was evaluated using specificity sensitivity and Area Under Curve AUC score as parameter A prototype of the classification model was implemented using Keras Open source deep learning framework in Python Programming Language The AUC ROC curve of the model was able to classify Atelestasis Support devices Pleural effusion Pneumonia A normal CXR no finding Pneumothorax and Consolidation However Lung opacity and Cardiomegaly had probability out of less than 0 5 and thus were classified as absent Precision recall and F1 score values were 0 78 this imply that the number of False Positive and False Negative are the same revealing some measure of label imbalance in the dataset The study concluded that the developed model is sufficient to classify abnormalities present in chest radiographs into present or absent